HUBUNGAN KEBAHAGIAAN KERJA DENGAN WORK ENGAGEMENT PADA APARATUR SIPIL NEGARA DI DINAS X KABUPATEN Y - I Nyoman Tri Arya Wiguna; I Gde Dhika Widarnandana, Wiriana (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research aims to determine the relationship between job happiness and work engagement in the State Civil Apparatus at the Population Control Service, Family Planning, Women's Empowerment and Child Protection, Badung Regency. The data collection process was carried out from June 1 2024 to July 1 2024. Work happiness was measured using the work happiness scale and work engagement was measured using the work engagement scale which had been tested for validity and reliability again. This research involved a sample of 70 people with an age range of 35-58 years. The data analysis method used in this research is the Pearson correlation test. Based on the results of the correlation analysis between the two variables, it can be concluded that there is a significant positive relationship between job happiness and work engagement.